A Decade of Research on Philippine Mammals: Progress and Challenges - Heaney, Lawrence R (Silliman Journal, 2022)
The mammal fauna of the Philippines is exceptionally rich in en dernic mammals, and also has a very high proportion of endangered species. Research during the period 1990 to 2000 has resulted in an improved understanding of the basic systematics of the 172 native land-mammal species known to be present. Some of the recently-discovered species have been formally described (but others have not), and a few identification keys are now available (but more are badly needed). Studies of comparative morphology, karyotypes, and protein allozymes have yielded information on phylogenetic relationships, but this topic remains poorly investigated. Published faunal surveys have produced the first compre-hensive inventories in the country yielding much crucial information on ecology and biogeography and the material for taxonomic studies, but many more are needed, and many unpublished surveys are not available. Biogeographic analyses have demonstrated that distributions of mammals have been profoundly influenced by the extent of Pleistocene islands and by climatic variation along elevational gradients in the many mountains of the Philippines. Each Pleistocene island is a unique center of biodiversity, and many high mountains (or mountain ranges) are unique subcenters. Patterns of genetic variation within species match very well with these Pleistocene islands, suggesting that speciation and diversification within the Philippines is intimately tied to this geological history. Further studies are needed to integrate phylogenetic information with biogeographic and ecological data. Ecological studies have demonstrated that species richness of some groups (e.g., bats) is highest in the lowlands, and that species richness of other ,croups (e.g., rodents) is highest at high elevations, often in lower mossy forest. Reproductive biology of fruit bats is well known from several studies, demonstrating that females of some small Philippine species are unique in being pregnant for 95% of their lives, but have low total reproductive output. The reproductive biology of most Philippine mammals remains poorly known or unknown. Population ecology and commu-nity ecology are well-known at a few sites, but generally poorly known at this time. We do know that many natural communities are very species-rich and that densities are often very high, and that native and non-native species often have very different patterns of habitat use, feeding ecology, movement, and longevity. Information on conservation status of mammals has improved greatly, with at least some information on distribution and abundance available for most species, and this allows us to estimate their decline in population due to destruction of habitat, and the relative vulnerability of most species. Recent studies of seed dispersal by fruit bats demonstrate their key role in naturally regenerating rain forest. Loss of about 94% of old-growth forest habitat has left many species highly vulnerable. The increase in number of protected areas (due in part to discovery of newspecies and biogeographic analysis) has improved the prospects for conservation, but more are needed Current knowledge is sufficient to guide some crucial conservation efforts, but much essential information is not currently available.